Marine-derived secondary metabolites in oncology: A comprehensive review - Samah S. Abuzahrah; Serag Eldin I. Elbehairi; Tahani Bakhsh; Ahmed Atwa; Nouf Juaid; Reham Hassan Mekky (Current Research in Biotechnology)
Marine-derived secondary metabolites are emerging as promising anticancer agents due to their structural diversity and potent bioactivity. Within the scope of this all-encompassing study, the most recent advancements in the identification, characterization, and therapeutic applications of marine-derived compounds in oncology are studied. In this review, we discuss various types of bioactive metabolites that are significant, such as macrolactins, polyketides, terpenes, and peptides that are derived from diverse marine organisms viz., bacteria, fungi, actinomycetes, microalgae, macroalgae, mangroves, sponges, coral reefs, mollusks, and echinodermata Unique compounds from marine organisms exhibit diverse mechanisms that selectively target cancer cells. This minimizes harm to healthy tissues and reduces side effects.“These metabolites interfere with key cancer progression pathways such as immune modulation, apoptosis, angiogenesis, metastasis, and cell cycle regulation. Additionally, they enhance conventional treatments like chemotherapy and immune therapy by overcoming drug resistance, particularly multidrug resistance (MDR) and the persistence of cancer stem cells (CSCs), major contributors to therapy failure. CSCs, characterized by self-renewal and therapy resistance, play a central role in tumor recurrence and drug resistance. This review highlights the novelty of marine metabolites, providing a comprehensive inventory of their clinical and commercial applications while emphasizing their role in advancing green medicine through sustainable drug discovery practices. This review shows the promise of marine-derived secondary metabolites in building the future of cancer therapies by incorporating insights from current studies. It also inspires further exploration of the development of these metabolites as clinically practicable treatments.